Assessment of the accuracy of digital surgical planning and its implementation with tibial plateau levelling osteotomy - Henry Todd; Jack Fawsitt; Nicholas Goody; Darren James Shaw; Dylan Neil Clements (Veterinary Research Communications, 2026)
Introduction Pre-operative planning of orthopaedic procedures is widely regarded as critical to their safe execution; however, the ability to both accurately plan and enact the plan have not been assessed in the veterinary context. The aim of this study was to assess the ability of boarded surgeons compared to surgical trainees to reproducibly plan a TPLO and then to implement this plan in vivo and in vitro . Methods Twelve participants planned 10 TPLOs from blinded radiographs of dogs diagnosed with cranial cruciate ligament disease; this was repeated four weeks later and compared between surgical groups using linear mixed-effect models (LME). To assess the ability of a participant to implement their pre-operative planning in vivo , pre-operative TPLO plans were compared to post-operative radiographs for each patient using LME in 6 participants. In vitro , three 3D printed tibial models were provided to 8 surgeons. Each participant was asked to perform a TPLO osteotomy to predefined measurements and accuracy of this osteotomy was compared between groups using LME Results Neither the accuracy of pre-operative planning, nor the ability to accurately implement the plan at surgery, consistently changed with surgeon experience. Using 3D printed models, surgical trainees differed significantly from predetermined D1 ( p = 0.019), D2 ( p = 0.002) values and carried out significantly distomedial to proximolateral angled osteotomies ( p < 0.001). However, surgical trainees and board-certified surgeons were not significantly different from each other when assessing the accuracy of in vitro osteotomies. Conclusion Pre-operative planning is accurate across differing experience levels and is a valuable tool for the safe execution of canine TPLOs. Accuracy of implementation of the plan during surgery is similar between groups, but surgical trainees were less accurate than residency trained surgeons when undertaking TPLO osteotomies on tibial models. This highlights the critical requirement for intra-operative supervision of surgical trainees.

Pharmacokinetics and Pharmacodynamics of Nomlabofusp in Non-clinical Studies of Friedreich’s Ataxia - Flavia De Toni; Vanessa Ragaglia; Devin Schecter; Angela S. Miller; Eric Gonzalez; Erik J. Wagner; Xin Xu; R. Mark Payne; Jean-Nicholas Mess; Matthew G. Baile; Adrienne Clements-Egan; Gopi Shankar (The AAPS Journal, 2025)
Nomlabofusp is a cell penetrant peptide-based recombinant fusion protein designed to enter cells and deliver human frataxin into the mitochondria of adults and children with Friedreich’s ataxia. In this article we present non-clinical studies evaluating the pharmacology of nomlabofusp, including in a murine striated muscle tissue frataxin knockout model of Friedreich’s ataxia. We demonstrate that subcutaneous administration of nomlabofusp distributes in a dose-dependent manner to several organs including the dorsal root ganglion, heart, and skeletal muscle, which are known to be predominantly affected in Friedreich’s ataxia, as well as to other tissues, including skin. Plasma nomlabofusp concentrations correlated with levels of human frataxin delivered by nomlabofusp into tissues, and the increases in frataxin were correlated amongst tissues, especially with skin. In the knockout mice, we show that the pharmacokinetics and processing of nomlabofusp were comparable with wild type animals and that treatment with nomlabofusp halts the progression of cardiac dysfunction and significantly increased survival. Together, the findings from these non-clinical studies demonstrate that nomlabofusp exposure increases human frataxin in Friedreich’s ataxia-relevant tissues and provide evidence of pharmacologic effects. Graphical Abstract

Finding explanations for weak economic complexity in resource-rich African countries: Exploring the role of natural resource endowment and institutional quality - Clement Olalekan Olaniyi; Nicholas Mbaya Odhiambo (Resources Policy, 2025)

Perceived constraints to participating in wildlife-related recreation - Nicholas W. Cole; Emily J. Wilkins; Kaylin R. Clements; Rudy M. Schuster; Ashley A. Dayer; H.W. Harshaw; David C. Fulton; Jennifer N. Duberstein; Andrew H. Raedeke (Journal of Outdoor Recreation and Tourism, 2024)

Features of turbulence during wildland fires in forested and grassland environments - Ajinkya Desai; Warren E. Heilman; Nicholas S. Skowronski; Kenneth L. Clark; Michael R. Gallagher; Craig B. Clements; Tirtha Banerjee (Agricultural and Forest Meteorology, 2023)

The relative importance of COVID‐19 pandemic impacts on biodiversity conservation globally - David W. Gibbons; Chris Sandbrook; William J. Sutherland; Rezvin Akter; Richard Bradbury; Steven Broad; Andy Clements; Humphrey Q. P. Crick; Joanna Elliott; Ngawang Gyeltshen; Melanie Heath; Jonathan Hughes; et al. (Conservation Biology, 2022)
The COVID‐19 pandemic has had an enormous impact on almost all aspects of human society and endeavor; the natural world and its conservation have not been spared. Through a process of expert consultation, we identified and categorized, into 19 themes and 70 subthemes, the ways in which biodiversity and its conservation have been or could be affected by the pandemic globally. Nearly 60% of the effects have been broadly negative. Subsequently, we created a compendium of all themes and subthemes, each with explanatory text, and in August 2020 a diverse group of experienced conservationists with expertise from across sectors and geographies assessed each subtheme for its likely impact on biodiversity conservation globally. The 9 subthemes ranked highest all have a negative impact. These were, in rank order, governments sidelining the environment during their economic recovery, reduced wildlife‐based tourism income, increased habitat destruction, reduced government funding, increased plastic and other solid waste pollution, weakening of nature‐friendly regulations and their enforcement, increased illegal harvest of wild animals, reduced philanthropy, and threats to survival of conservation organizations. In combination, these impacts present a worrying future of increased threats to biodiversity conservation but reduced capacity to counter them. The highest ranking positive impact, at 10, was the beneficial impact of wildlife‐trade restrictions. More optimistically, among impacts ranked 11‐20, 6 were positive and 4 were negative. We hope our assessment will draw attention to the impacts of the pandemic and, thus, improve the conservation community's ability to respond to such threats in the future.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos - Nicholas M. A. Smith; Boris Yagound; Emily J. Remnant; Charles S. P. Foster; Gabriele Buchmann; Michael H. Allsopp; Clement F. Kent; Amro Zayed; Stephen A. Rose; Kitty Lo; Alyson Ashe; Brock A. Harpur; et al. (Molecular Ecology, 2020)
The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele .

Synchronous biological feedbacks in parrotfishes associated with pantropical coral bleaching - Brett M. Taylor; Cassandra E. Benkwitt; Howard Choat; Kendall D. Clements; Nicholas A. J. Graham; Mark G. Meekan (Global Change Biology, 2020)
Biological feedbacks generated through patterns of disturbance are vital for sustaining ecosystem states. Recent ocean warming and thermal anomalies have caused pantropical episodes of coral bleaching, which has led to widespread coral mortality and a range of subsequent effects on coral reef communities. Although the response of many reef‐associated fishes to major disturbance events on coral reefs is negative (e.g., reduced abundance and condition), parrotfishes show strong feedbacks after disturbance to living reef structure manifesting as increases in abundance. However, the mechanisms underlying this response are poorly understood. Using biochronological reconstructions of annual otolith (ear stone) growth from two ocean basins, we tested whether parrotfish growth was enhanced following bleaching‐related coral mortality, thus providing an organismal mechanism for demographic changes in populations. Both major feeding guilds of parrotfishes (scrapers and excavators) exhibited enhanced growth of individuals after bleaching that was decoupled from expected thermal performance, a pattern that was not evident in other reef fish taxa from the same environment. These results provide evidence for a more nuanced ecological feedback system—one where disturbance plays a key role in mediating parrotfish–benthos interactions. By influencing the biology of assemblages, disturbance can thereby stimulate change in parrotfish grazing intensity and ultimately reef geomorphology over time. This feedback cycle operated historically at within‐reef scales; however, our results demonstrate that the scale, magnitude, and severity of recent thermal events are entraining the biological responses of disparate communities to respond in synchrony. This may fundamentally alter feedbacks in the relationships between parrotfishes and reef systems.

Testing the single-pass VOC removal efficiency of an active green wall using methyl ethyl ketone (MEK) - Fraser Torpy; Nicholas Clements; Max Pollinger; Andy Dengel; Isaac Mulvihill; Chuan He; Peter Irga (Air Quality, Atmosphere & Health, 2018)

Opsins have evolved under the permanent heterozygote model: insights from phylotranscriptomics of Odonata - Anton Suvorov; Nicholas O. Jensen; Camilla R. Sharkey; M. Stanley Fujimoto; Paul Bodily; Haley M. Cahill Wightman; T. Heath Ogden; Mark J. Clement; Seth M. Bybee (Molecular Ecology, 2017)
Gene duplication plays a central role in adaptation to novel environments by providing new genetic material for functional divergence and evolution of biological complexity. Several evolutionary models have been proposed for gene duplication to explain how new gene copies are preserved by natural selection, but these models have rarely been tested using empirical data. Opsin proteins, when combined with a chromophore, form a photopigment that is responsible for the absorption of light, the first step in the phototransduction cascade. Adaptive gene duplications have occurred many times within the animal opsins’ gene family, leading to novel wavelength sensitivities. Consequently, opsins are an attractive choice for the study of gene duplication evolutionary models. Odonata (dragonflies and damselflies) have the largest opsin repertoire of any insect currently known. Additionally, there is tremendous variation in opsin copy number between species, particularly in the long‐wavelength‐sensitive ( LWS ) class. Using comprehensive phylotranscriptomic and statistical approaches, we tested various evolutionary models of gene duplication. Our results suggest that both the blue‐sensitive ( BS ) and LWS opsin classes were subjected to strong positive selection that greatly weakens after multiple duplication events, a pattern that is consistent with the permanent heterozygote model. Due to the immense interspecific variation and duplicability potential of opsin genes among odonates, they represent a unique model system to test hypotheses regarding opsin gene duplication and diversification at the molecular level.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Quantifying landscape‐level methane fluxes in subarctic Finland using a multiscale approach - Iain. P. Hartley; Timothy. C. Hill; Thomas. J. Wade; Robert. J. Clement; John. B. Moncrieff; Ana. Prieto‐Blanco; Mathias. I. Disney; Brian. Huntley; Mathew. Williams; Nicholas. J. K. Howden; Philip. A. Wookey; Robert. Baxter (Global Change Biology, 2015)
Quantifying landscape‐scale methane ( CH 4 ) fluxes from boreal and arctic regions, and determining how they are controlled, is critical for predicting the magnitude of any CH 4 emission feedback to climate change. Furthermore, there remains uncertainty regarding the relative importance of small areas of strong methanogenic activity, vs. larger areas with net CH 4 uptake, in controlling landscape‐level fluxes. We measured CH 4 fluxes from multiple microtopographical subunits (sedge‐dominated lawns, interhummocks and hummocks) within an aapa mire in subarctic Finland, as well as in drier ecosystems present in the wider landscape, lichen heath and mountain birch forest. An intercomparison was carried out between fluxes measured using static chambers, up‐scaled using a high‐resolution landcover map derived from aerial photography and eddy covariance. Strong agreement was observed between the two methodologies, with emission rates greatest in lawns. CH 4 fluxes from lawns were strongly related to seasonal fluctuations in temperature, but their floating nature meant that water‐table depth was not a key factor in controlling CH 4 release. In contrast, chamber measurements identified net CH 4 uptake in birch forest soils. An intercomparison between the aerial photography and satellite remote sensing demonstrated that quantifying the distribution of the key CH 4 emitting and consuming plant communities was possible from satellite, allowing fluxes to be scaled up to a 100 km 2 area. For the full growing season (May to October), ~ 1.1–1.4 g CH 4 m −2 was released across the 100 km 2 area. This was based on up‐scaled lawn emissions of 1.2–1.5 g CH 4 m −2 , vs. an up‐scaled uptake of 0.07–0.15 g CH 4 m −2 by the wider landscape. Given the strong temperature sensitivity of the dominant lawn fluxes, and the fact that lawns are unlikely to dry out, climate warming may substantially increase CH 4 emissions in northern Finland, and in aapa mire regions in general.

Ambient Coarse Particulate Matter and Human Health: A Systematic Review and Meta-Analysis - Sara D. Adar; Paola A. Filigrana; Nicholas Clements; Jennifer L. Peel (Current Environmental Health Reports, 2014)